MODELING OF MHD OSCILLATORY BLOOD FLOW IN A CHANNEL AS MICROPOLAR FLUID IN THE PRESENCE OF CHEMICAL REACTION - Oahimire, J. I.; Olajuwon, B. I. (FUDMA JOURNAL OF SCIENCES, 2022)
MHD oscillatory blood flow in a channel as micropolar fluid in the presence of chemical reaction and a transverse magnetic field are studied. The partial differential equations governing the flow were formulated base on assumptions and already existing model. The partial differential equations were transformed to dimensionless equations with suitable variables. Analytical solution was obtained for the dimensionless equations. The pertinent parameters were investigated with graphs plotted and table generated using Matlab software. The study reveals that the parameters has significant influences on the flow.